PEMBELAJARAN KEWIRAUSAHAAN DAN MINAT BERWIRAUSAHA BERBASIS AGRO DAN MARINE PADA MAHASISWA AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS TEUKU UMAR - Ika Rahmadani; Almira Keumala Ulfah; Azmir Gani (Universitas Teuku Umar, 2020)
The purpose of this study was to determine the effect of entrepreneurship learning on the interest in entrepreneurship based on agro and marine industry for accounting students at the Faculty of Economics, Teuku Umar University. Respondents in this study were active students in the Accounting Study Program who had taken Entrepreneurship courses. Obtained 82 questionnaires received and can be used for analysis. By using Regression Analysis, the results of this study indicate that entrepreneurial learning has an influence on students' interest in entreprenership